Jørgen Christian Bang & Jørgen Døør - Os Organizadores (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2020)
Jørgen Christian Bang was born in 1946 in Odense, Denmark. He studied Music, Philosophy, Latin (Copenhagen University 1965-66), and Danish, Nordic, German, and Scandinavian Languages and Literatures, Linguistics, (Odense University 1966-74). He was Associated Professor in Danish Language & Communication (OU/SDU 1974-2018). In 2018 he became Professor Emeritus. Students rebellion and Union representative for students 1966-74; and for researchers and teachers 1976-2018. Member of the Board of the University of Southern Denmark 2012-2018 representing the scientific staff. Working for democracy, freedom and equality, “Education and research for life and people, not for profit”. Practicing music in amateur symphony orchestras and choir; free school, climate and peace movement. An ecological way of life together with his wife Anne; five children and eight grandchildren. Jørgen Døør was born in 1933 in Copenhagen, Denmark. Studies of Philosophy and Psychology, University of Copenhagen; Mathematics and Nordic Languages, Teachers Training College, Copenhagen. Head of Department, University of Southern Denmark. (OU 1966-1997). At present: Free-lance researcher, novelist (published 14 novels with his wife, Dorte Bay Madsen), pacifist, vegetarian, and ecological activist.